ABDI DALEM DAN ABDI NEGARA: IDENTITAS GANDA SENIMANPRIYAYI KEMLAYAN SURAKARTA 1950-AN-1970-AN - Heri Priyatmoko (Faculty of Humanities, Jember University, 2013)
This article explains the identity of artist-priyayi in Kemlayan, Surakarta during the postcolonial period. Kasunanan court did not have the authority to keep abdi dalem to serve the king after the independence of Indonesia. The king could not guarantee the finance of pangrawit in Kemlayan. The question to respond the situation is what cultural political strategy was used by the artistpriyayi community in Kemlayan to deal with the changing era? How was their identity after the social class was omitted?With expertise in art, the artist-priyayi in Kemlayan joint art institution that belonged to the Indonesian government to become abdi negara. They were helping Keraton Kasunanan by joining in traditional events. Then they got new identity without losing their the previous one, as abdi dalem. They also kept their priyayi’s attributes. Strategy that was used by the artistpriyayi in Kemlayan brought a positive outcome. They have double identity and the functional role as artists remained although keraton hegemony was gone. Their work orientation was not serving the king anymore. Now they serve people in culture sector according the government’s plan. Their identity as priyayi was admitted by the people and government as respect for their contribution. Keywords: artists, priyayi, abdi dalem, hegemony, identity